Pembelajaran Etnomatematika Sunda untuk Meningkatkan Kemampuan Pemodelan Matematik dan Kecerdasan Kreatif Mahasiswa PGSD - Supriadi Supriadi (Universitas Pendidikan Indonesia Kampus Serang, 2019)
Aspects of local culture in learning mathematics in primary school teacher education are still not optimally presented in learning. One way to realize this learning is by learning Sundanese ethnomathematics. The mathematical modeling is very supportive ability in the learning process. The process of mathematical modeling can develop creative intelligence. This article uses the Didactical Design Research method to further optimize the quality of teaching materials. The number of research subjects was 180 of first semester student. The teaching material was tested for success by an experimental method through a test instrument that measured mathematical modeling abilities and creative intelligence. Research results in mathematical modeling ability among students who get mathematics learning using Sundanese ethnomathematics learning is significantly better than students who use conventional learning. There is no interaction between learning models used with educational background groups on mathematical modeling abilities. There is no interaction for creative intelligence. Sundanese ethnomathematics learning with didactic design material can be used as a model of mathematics learning to develop the abilities and dispositions of mathematical creative thinking abilities and dispositions in the elementary school teacher education environment.